Adaptive time‐ and location‐aware routing in telecom mesh networks. Issue 1 (1st March 2013) - Dikbiyik, Ferhat; Mukherjee, Biswanath; Tornatore, Massimo
Abstract : In telecom mesh networks, connections can be provisioned considering their availability requirements. A connection's availability can be estimated based on the links' statistical availability (e.g., depending on historical failure occurrences and repair times).The authors remark that the actual failure statistics depend on (i) when and (ii) where a connection is routed (as failure rates throughout the year and in different locations may be different). Moreover, the failure rate is not homogeneous along a link and a detailed time‐ and location‐aware availability calculation is required. Most link failures are caused by dig‐ups, thus there is a direct relationship between construction works, which require excavations, and link failures. So, the probability of a link failure at a certain location depends on (i) the time/day when dig‐up works are performed and (ii) population of the location (assuming that the more crowded the location is, the more constructions occur). By exploiting the time‐ and location‐dependent failure information, the authors investigate a novel adaptive time‐ and location‐aware routing scheme, which provisions connections on highly available paths depending on a connection's duration and availability requirements. The authors' approach shows significant upgrade‐cost savings, while satisfying the service requirements, compared with traditional approaches.